Efficient expression and bound for pairwise error probability in Rayleigh fading channels, with application to union bounds for-turbo codes - Ince, EA; Kambo, NS; Ali, SA (IEEE-Inst Electrical Electronics Engineers Inc, 2005)
This work provides a new exact expression for the pairwise error probability. under perfect channel state information. Using this expression, the average union upper bounds for (1, 7/5, 7/5) and (1, 5/7, 5/7) turbo coding schemes are presented based on transfer function approach assuming fully interleaved Rayleigh fading channels. Derivation for the pairwise error probability leads to a compact approximation which overlaps with the exact expression. This new approximation is computationally more efficient than the existing ones, and leads to a much quicker generation of union bounds for performance analysis.
Keywords: average union upper bound; pairwise error probability; perfect channel state information; turbo codes